Assessing the Impact of Rural Development for the Agro-Industrial Complex of the Russian Federation - N. A. Vladimirov (Статистика и экономика)
Modern agro-industrial complex should combine both the most modern digital and innovative developments and traditional, time-tested agricultural technologies. It is an indisputable fact that without a labor force - people who are ready to work in rural areas, there will be no development of the agro-industrial complex. In 2021, the rural population in Russia decreased by 3.5% compared to 2015, while the working-age population in rural areas decreased by 4.6% over the same period. At the same time, the demand and consumption of agricultural products remains extremely high, so in 2021, compared to 2015, the consumption of meat and meat products in the Russian Federation increased by 6.8%, fruits and berries by 5.0%, milk by 3,4%, eggs by 2.9%, vegetables and melons by 2.0%. The relevance of the topic is confirmed by a set of measures developed by the Ministry of Agriculture of the Russian Federation, which are aimed at improving the living standards of rural citizens and combating the so-called “village crisis”. For these purposes, on May 31, 2019, the Decree of the Government of the Russian Federation No. 696 approved the program “Integrated Development of Rural Territories”. It implies not only the preservation of the rural population and the improvement of the life of rural citizens, but also the increase in the efficiency of traditional agriculture and the development of modern industries in rural areas.Purpose of the study. In the context of sanctions pressure and unpredictable consequences for the Russian economy, the state and domestic agrarians should take special responsibility for the stability of the agro-industrial sector. In this regard, it is necessary to prevent possible risks for the industry at an early stage and assess the possibilities for its development in the regional context. The purpose of the study is to assess the impact of the development of rural areas on the agro-industrial complex of the Russian Federation. It is necessary to determine the differentiation of Russian regions in terms of the level of development of rural areas and assess the impact of their development on the agro-industrial complex.Materials and methods. The source of data for the study is data from the Russian Population Census (2010 and 2020), the Agricultural Micro-Census 2021, and Sample Survey of the Labor Force for 2010-2021. These data allow us to draw conclusions about the state of rural areas, the level of their development and determine the potential of the agro-industrial complex of the region. In addition, the paper differentiates the regions of Russia, using the method of hierarchical clustering, according to the level of development of rural areas with a linkage to the development of the agro-industrial complex of the region.Results. The results obtained based on the data of the Russian Population Census 2020 on the share of rural settlements with a population of less than 10 people indicate that in the European territory of Russia the share of “extinct” rural settlements becomes maximum closer to the north. With a shift to the South, their share is significantly reduced. The most densely populated rural areas should be considered: the Republic of Crimea (2.6%), the Stavropol Territory (3.0%), the Republic of Dagestan (4.5%), the Krasnodar Territory (4.6%), the Chechen Republic (8.1%) and the Rostov region (8.3%). The share of the working-age population in rural areas, employed in agriculture is systematically decreasing from year to year and in 2021, according to the Survey of the Labor Force, it reached 17.3%. The largest share of the working-age population in rural areas, employed in agriculture is noted in the Chechen Republic (35.1%), Tambov (35.0%), Belgorod (29.7%), Kirov (29.7%) and Saratov regions (29,1%).The growth rate of agricultural products in 2021 in 2010 prices, compared to 2010, amounted to 56.8%. At the same time, livestock production is growing much faster, surpassing the growth rate of crop production. In 2021, livestock production in 2010 prices increased by 105.0%, compared to 2010, the increase in crop production over the same period was only 18.4%.Cluster analysis divided 85 regions of Russia into 6 clusters, in accordance with their level of development of rural areas (the share of rural settlements with a population of less than 10 people; the share of the working-age population in rural areas, employed in agriculture) and the level of development of the agro-industrial complex (the share of agricultural land in the total area of the territory of the subject; the growth rate of agricultural products in 2021 in prices of 2010, in% of 2010). In the course of the analysis, regions were identified as leaders in the industry and regions with certain problems, the elimination of which will enable the growth of the agro-industrial complex.Conclusion. The paper pays special attention to the development of rural areas; the author considers the regions of Russia with a share of rural settlements with a population of less than 10 people as “endangered” settlements. Such villages can no longer develop agriculture and be points of growth for the agro-industrial complex in the region. Particular attention is paid to the share of the workingage population in rural areas, employed in agriculture, since these people are now the basis of agriculture and their work contributes to the development of the industry. The state of the agro-industrial complex in the region is assessed using the share of agricultural land in the total area of the territory of the subject and the growth rate of agricultural products. These indexes reflect the demand for the agricultural industry in the region; show the importance of the industry and the prospects for its development.Based on these indexes, the cluster analysis of the constituent entities of the Russian Federation identified six groups of regions with similar vectors for the development of the agro-industrial complex. The first cluster included the most stable regions in the agricultural sector, with a high proportion of the working-age population in rural areas, employed in agriculture, a large share of agricultural land and a high growth rate of agricultural products. The second cluster was filled with extremely low potential for the development of the agro-industrial complex - the regions of Siberia, the European North and the Far East. The third cluster contains regions with the greatest potential for the development of the agro-industrial complex. The fourth cluster includes regions in which there is a “stagnation” in the agricultural sector. The regions of the fifth cluster need to increase the workingage population, ready to engage in agriculture, in which case they are provided with a significant increase in agricultural production. The sixth cluster consists of industry leaders; however, they should develop the industry by attracting more people to agriculture, as well as expanding farmland areas.